Living in urban areas due for redevelopment: views of children and their families in Addis Ababa and Hawassa - Pankhurst, A; Tiumelissan, A (Young Lives, 2013)
This report is the first of three resulting from a sub-study conducted by Young Lives in four communities in Ethiopia, three in Addis Ababa and one in Hawassa, to examine what happens to children and their families living in areas that are due to be redeveloped. The paper presents the views of children and their caregivers about their living conditions prior to the impending move. It considers how children and adults view their home and neighbourhood environment and the extent of their social support networks. The report seeks to document how children and caregivers understand and experience their lives in a context of urban poverty, living in sites which are considered to be ‘slums’, mainly in areas that are due to be demolished and redeveloped through urban renovation programmes involving both commercial and residential development. The evidence from this study suggests that children and their families live in crowded and insalubrious conditions in these urban sites. Most households do not own their homes. Children dislike their lack of separate kitchens, latrines, and washing facilities, and more than half the caregivers thought that their neighbourhoods were bad places to bring up children. Despite the conditions of material deprivation, the children and their caregivers value the cohesive social relations. Relations with family and friends are important for children, and they liked living close to their friends, schools, markets, cafés and religious institutions. Relocation could bring about improvements in their housing and neighbourhood, although this will depend on where they are relocated to, what services and opportunities for work are available, and whether families will be able to afford the new condominium housing on offer. Family relations and school conditions are likely to be crucial for children, whereas caregivers will need to rebuild social networks, and funeral, religious and credit associations can be expected to play a key role in the successful adaptation of relocated households.